ENGLISH TASK TO DEVELOP THE STUDENTS’ COMMUNICATIVE COMPETENCE: A STUDY OF EDUKATIF WORK BOOK FOR JUNIOR HIGH SCHOOL STUDENTS - Dyah Rohma Wati; Endang Fauziati; Abdillah Nugroho (Universitas Muhammadiyah Surakarta, 2013)
This study is mainly intended to find out the extent to which tasks in English work books are designed to develop the students’ communicative competence. The objective of this study is to describe how the tasks in Edukatif work books are designed to develop students’ discourse competence, linguistic competence, actional competence, sociolinguistic competence, and strategic competence. This study is a qualitative research which involves content analysis approach. The data are the tasks in Edukatif work books used by eight grade students of the first and second semester. In collecting the data, the writer uses documentation method. The data analysis used Huberman and Miles’ concept which involves data reduction, data display and verification. The findings show that among the five competences and its components of communicative com- petence, some components are not well developed in the work books. The tasks develop all components of discourse competence except one aspect in linguistic competence, that is, phonology. The tasks develop all components of actional competence except the speech act. The tasks develop components of sociolinguistic competence except the cultural and non-verbal communicative factor. The tasks develop only one component of strategic competence, that is, time gaining strategy. The conclusion is that the tasks in Edukatif work books are sufficient to develop the students’ discourse, linguistic, and actional competence. The tasks, however, are not sufficient to develop students’ sociolinguistic and strategic competence.